2014
DOI: 10.1657/1938-4246.46.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Two Bogs in the Canadian Hudson Bay Lowlands and a Temperate Bog Reveal Similar Annual Net Ecosystem Exchange of CO2

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 38 publications
5
49
1
Order By: Relevance
“…Carbon dioxide exchange was typical of a raised bog, with net CO 2 sink being rather high (202 gC m −2 for MayAugust) but within the range of previous observations (IPCC, 2014(IPCC, , 2013. The remarkably wet weather of 2015 ensured high moisture availability and thus promoted high photosynthesis during the sunny periods.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Carbon dioxide exchange was typical of a raised bog, with net CO 2 sink being rather high (202 gC m −2 for MayAugust) but within the range of previous observations (IPCC, 2014(IPCC, , 2013. The remarkably wet weather of 2015 ensured high moisture availability and thus promoted high photosynthesis during the sunny periods.…”
Section: Discussionsupporting
confidence: 77%
“…For the period of May-July with the best data coverage, the corresponding values were −186, 91, and 277 gC m −2 . The Mukhrino May-August GPP falls between 224 and 243 gC m −2 observed over the same period by two Canadian bogs and 466-539 gC m −2 in Mer Bleue (Humphreys et al, 2014). However, in terms of net summer uptake, the Mukhrino was among the highest estimates.…”
Section: Carbon Exchangementioning
confidence: 72%
“…Previously, Humphreys et al (2014) presented 2-years of NEE for two bogs located in the Hudson Bay lowlands. There have been long-term measurements (more than 4-years) from a temperate bog (Lafleur et al 2003;Roulet et al 2007), a minerogenic fen Nilsson et al 2008;Peichl et al 2014), palsa mire (Aurela et al 2001(Aurela et al , 2002(Aurela et al , 2004, blanket bog (Sottocornola and Kiely 2010;Koehler et al 2011) and treed fen (Flanagan and Syed 2011).…”
Section: Discussionmentioning
confidence: 99%
“…found on hummocks tend to increase productivity to grow away from the water table, in an attempt to reach a preferential position relative to the water table (Belyea and Clymo 1999;Bridgham et al 2008). Humphreys et al (2014) observed a decrease in GEP in bogs in the Hudson Bay lowlands during periods where the WTD was far from surface. Similarly, Sulman et al (2010) previously showed that a temperate bog's GEP and ER increased as the WTD moved closer to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The Hudson Bay Lowlands (HBL) of central Canada comprise the second largest contiguous peatlands in the world, containing an estimated 12% of the organic carbon stored in Canadian soils (Humphreys et al, 2014). It is a region characterized by low topographic relief that is overlain with poorly drained glacial and marine silts and clays, with lakes and ponds covering an estimated 25% (Macrae et al, 2004) to >40% of the landscape (Bello and Smith, 1990).…”
Section: Introductionmentioning
confidence: 99%